Evaluation of performance and cargo-shock of an autonomous handling system for container unloading - Jasper Wilhelm; Nils Hendrik Hoppe; Christoph Petzoldt; Lennart Rolfs; Michael Freitag (Logistics Research, 2022)
In the business-to-business sector large quantities of the internationally traded goods are transported by hundreds in identical parcels inside shipping containers. These parcels are often unloaded manually, which is labor-intensive and physically demanding. In previous papers, we presented a novel semi-autonomous container unloading system and an estimation of the performance. In this paper we evaluate the proposed system. Tests are performed in a laboratory testbed with a container and different sized parcels. We use this testbed to record the times for individual tasks of the system as well as the acceleration of the parcels. For comparison, we test the acceleration in the manual and bulk unloading scenario. Following a line-by-line approach, the proposed system's performance ranges from 261 to 3,014 parcels per hour, between manual and bulk performance. The throughput depends on the parcel's size and is higher for small parcels. With a maximum shock on the parcels of less than the proposed system induces significantly less force than other approaches (manual and bulk).
Keywords: 650; Anonomous Systems; Container Unloading; Cyber-Physical Systems; System validation; Performance Evaluation; Shock (mechanics); Packproblem; Roboter; Performance-Messung